On the differential advantages of evergreenness and deciduousness in mediterranean oak woodlands: a flux perspective - Baldocchi, Dennis D.; Ma, Siyan; Rambal, Serge; Misson, Laurent; OURCIVAL, JEAN-MARC; Limousin, Jean-Marc; Pereira, João; Papale, Dario (ECOLOGICAL APPLICATIONS, 2010)
We assessed the differential advantages of deciduousness and evergreenness by examining 26 site-years of carbon dioxide, water vapor, and energy flux measurements from five comparable oak woodlands in France, Italy, Portugal, and California (USA). On average, the evergreen and deciduous oak woodlands assimilated and respired similar amounts of carbon while using similar amounts of water. These results suggest that evergreen and deciduous woodlands have specific, and similar, ecological costs in mediterranean climates, and that both leaf habits are able to meet these costs. What are the mechanisms behind these findings? Deciduous oaks compensated for having a shorter growing season by attaining a greater capacity to assimilate carbon for a given amount of intercepted solar radiation during the well-watered spring period; at saturating light levels, deciduous oaks gained carbon at six times the rate of evergreen oaks. Otherwise, the two leaf habits experienced similar efficiencies in carbon use (the change in carbon respired per change in carbon assimilated), water use (the change in carbon assimilation per change in water evaporated), and rainfall use (the change in evaporation per change in rainfall). Overall, leaf area index, rather than leaf habit, was the significant factor in determining the absolute magnitude of carbon gained and water lost by each evergreen and deciduous oak woodland over an annual interval; the closed canopies assimilated and respired more carbon and transpired more water than the open canopies. Both deciduous and evergreen mediterranean oaks survive in their seasonally hot/dry, wet/cool native range by ensuring that actual evaporation is less than the supply of water. This feat is accomplished by adjusting the leaf area index to reduce total water loss at the landscape scale, by down-regulating photosynthesis, respiration, and stomatal conductance with progressive seasonal soil water deficits, and by extending their root systems to tap groundwater.
The following values have no corresponding Zotero field: pub-location: 1990 M STREET NW, STE 700, WASHINGTON, DC 20036 USA publisher: ECOLOGICAL SOC AMER
Keywords: carbon dioxide exchange; deciduousness vs. evergreen